The interaction between cellular senescence and chronic kidney disease as a therapeutic opportunity - Zhao, Jing-Li; Qiao, Xiao-Hui; Mao, Jian-Hua; Liu, Fei; Fu, Hai-Dong (Frontiers in Pharmacology, 2022)
Chronic kidney disease (CKD) is an increasingly serious public health problem in the world, but the effective therapeutic approach is quite limited at present. Cellular senescence is characterized by the irreversible cell cycle arrest, senescence-associated secretory phenotype (SASP) and senescent cell anti-apoptotic pathways (SCAPs). Renal senescence shares many similarities with CKD, including etiology, mechanism, pathological change, phenotype and outcome, however, it is difficult to judge whether renal senescence is a trigger or a consequence of CKD, since there is a complex correlation between them. A variety of cellular signaling mechanisms are involved in their interactive association, which provides new potential targets for the intervention of CKD, and then extends the researches on senotherapy. Our review summarizes the common features of renal senescence and CKD, the interaction between them, the strategies of senotherapy, and the open questions for future research.